1995
DOI: 10.1007/bf02071318
|View full text |Cite
|
Sign up to set email alerts
|

Molecular neurobiology and pharmacology of the Vasopressin/Oxytocin receptor family

Abstract: 1. VP and OT mediate their wealth of effects via 4 receptor subtypes V1a, V1b, V2, and OT receptors. 2. We here review recent insights in the pharmacological properties, structure activity relationships, species differences in ligand specificity, expression patterns, and signal transduction of VP/OT receptor. 3. Furthermore, the existence of additional VP/OT receptor subtypes is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(47 citation statements)
references
References 78 publications
0
47
0
Order By: Relevance
“…Since OT/vasopressin analogues bind to and activate four different receptor subtypes (OTR, V1a, V1b and V2) (Chini et al, 1995b;Peter et al, 1995;Barberis et al, 1999), peptides of potential clinical use should be checked for their receptor selectivity. Our competition experiments on receptor-rich membrane preparations showed that dLVT binds to human OTR, V1a, V1b and V2 with a pharmacological profile that is very similar to that of OT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since OT/vasopressin analogues bind to and activate four different receptor subtypes (OTR, V1a, V1b and V2) (Chini et al, 1995b;Peter et al, 1995;Barberis et al, 1999), peptides of potential clinical use should be checked for their receptor selectivity. Our competition experiments on receptor-rich membrane preparations showed that dLVT binds to human OTR, V1a, V1b and V2 with a pharmacological profile that is very similar to that of OT.…”
Section: Discussionmentioning
confidence: 99%
“…OT/AVP analogues bind to and activate (albeit with different affinities and efficacies) all members of the OT/AVP receptor family, which includes the OTR and the three vasopressin receptor subtypes V1a, V1b and V2 (Peter et al, 1995;Chini et al, 1995b;Barberis et al, 1999). When developing a specific OTR analogue, it is therefore essential to check its binding properties not only on the human OTR, but also on the V1a, V1b and V2 subtypes.…”
Section: Receptor Selectivitymentioning
confidence: 99%
“…However, the previous studies revealed that magnocellular VP could act as secretagogues for ACTH as well, reaching the anterior pituitary via several vascular pathways [15]. It was shown that VP binds to three G protein-coupled receptors, among which V1b receptors are primarily located at the corticotroph surface regulating ACTH secretion [16][17][18][19][20][21]. Although the role of VP in chronic stress response is well documented, it is still unclear how acute exposure to different types of stressors affects VP influence on ACTH secretion [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, VP secreted within the central nervous system (CNS), modulates neuronal function acting as a neurotransmitter. The functions of VP are mediated through membrane VP receptors belonging to the G proteincoupled membrane receptor (GPCR) superfamily (4). There are two major VP receptor subtypes, V1, which is coupled to calcium phospholipid dependent pathways, and V2, which is coupled to cAMP-dependent pathways.…”
Section: Introductionmentioning
confidence: 99%